Growth, Morphology and Growth Related Hormone Level in Kappaphycus alvarezii Produced by Mass Selection in Gorontalo Waters, Indonesia - Siti Fadilah; . Alimuddin; Petrus Rani Pong-Masak; Joko Santoso; Andi Parenrengi (HAYATI Journal of Biosciences, 2016)
The use of high quality seed can support the success of the seaweed cultivation. This study was conducted to evaluate the growth performance, morphology and growth related hormone level of brown strain seaweed Kappaphycus alvarezii seed produced by mass selection. Selection was performed in the Tomini Gulf, Gorontalo, based on mass selection of seaweed seed protocol with a slight modification in cut-off 10% of the highest daily growth rate. Selection was carried out for four generations. The selected 4thgeneration of seed was then used in cultivation performance test in the Celebes Sea, North Gorontalo, for three production cycles. The results showed that the selected K. alvarezii has higher clump weight and daily growth rate, longer thallus, more number of branches, and shorter internodes compared to the unselected control and seaweed from the farmer as external control. Furthermore, total sugar content, levels of kinetin hormone and kinetin:indole-3-acetic acid ratio were higher in selected seaweeds than that of unselected control and external control. Thus, mass selection method could be used to produce high growth of seed, and kinetin and indole-3-acetic acid play an important role in growth of K. alvarezii.